1995
DOI: 10.1507/endocrj.42.697
|View full text |Cite
|
Sign up to set email alerts
|

A Hyperthyroid Patient with Graves' Disease Who Was Strongly Resistant to Methimazole: Investigation on Possible Mechanisms of the Resistance.

Abstract: Abstract. We treated a patient who was hyperthyroid due to Graves' disease and strongly resistant to methimazole (MMI): in spite of good compliance, she needed 150 mg of MMI daily to control her hyperthyroidism.To elucidate the reasons of resistance to MMI, her serum and intrathyroidal MMI concentrations were determined by high pressure liquid chromatography (HPLC). After taking a 30 mg dose of MMI, she had a similar serum MMI concentration-time curve to that of a normal subject: drug malabsorption and rapid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Refractory cases have mostly shown resistance to high-dose thionamides and beta-blockers; rarely resistance to iodine has also been reported [1113, 1518]. In our patient, resistance to two different thionamides was seen.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Refractory cases have mostly shown resistance to high-dose thionamides and beta-blockers; rarely resistance to iodine has also been reported [1113, 1518]. In our patient, resistance to two different thionamides was seen.…”
Section: Discussionmentioning
confidence: 46%
“…Possible mechanisms mediating resistance in cases refractory to conventional treatment may range from drug malabsorption, rapid drug metabolism, antidrug antibodies, impairment of intrathyroidal drug accumulation or action, and predominant elevation of T3 rather than T4 levels [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Some cases of hyperthyroidism responding poorly to conventional doses of methyma- zole are described in the literature. An impairment of thyroid uptake of methimazole or of pathways after uptake is considered as possible mechanisms [17]. It is also reported that a high intrathyroidal iodine content due to amiodarone intoxication can reduce the effectiveness of thionamides [18].…”
Section: Discussionmentioning
confidence: 99%
“…(7)There are various reasons for possible resistance to carbimazole. These include malabsorption of the drug, rapid metabolism of the drug, antidrug antibodies and defects in intrathyroidal drug accumulation or action (4).…”
mentioning
confidence: 99%